1999
DOI: 10.2466/pms.1999.89.2.403
|View full text |Cite
|
Sign up to set email alerts
|

Eeg Correlates of Behavioural Laterality: Right-Handedness

Abstract: Among right-handers, the magnitude of differences in proficiency between the left and right hands varies considerably. Yet significance of the extent of right-handedness is still a controversial issue. To examine whether individual differences in asymmetry of hand skill can partly be attributed to individual differences in asymmetrical hemispheric activation, handedness and electroencephalographic (EEG) laterality were correlated in two large samples (ns = 60 and 128). Analysis indicated that part of the varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 34 publications
0
11
1
Order By: Relevance
“…Secondly the possible influence of handedness is tested with participants given a handedness questionnaire that measures handedness on a continuum rather than as a dichotomous variable. Consideration of hand preference as continuous may be particularly effective in the light of evidence showing degree of handedness to be related to magnitude of lateralization (Papousek & Schulter, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Secondly the possible influence of handedness is tested with participants given a handedness questionnaire that measures handedness on a continuum rather than as a dichotomous variable. Consideration of hand preference as continuous may be particularly effective in the light of evidence showing degree of handedness to be related to magnitude of lateralization (Papousek & Schulter, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…However, associations between ear dominance and cerebral laterality were not found over the whole cortex but only at certain locations. Regional specificity was also observed with respect to EEG correlates of extent of right-handedness (Papousek & Schulter, 1999a). This finding is further supported by observations that EEG asymmetries of different locations are only moderately correlated (Tomarken, et al, 1992;Papousek & Schulter, 1998) and that different measures of behavioural laterality, as well, are weakly correlated or not correlated at all (Boles, 1992;Hehge, Bloch, Cowin, Eng, Eviatar, & Sergent, 1994;Papousek & Schulter, 1999b).…”
Section: Resultsmentioning
confidence: 55%
“…In contrast to this approach it has been suggested (in connection with other lateraltty measures) that characteristic, temporally stable patterns of asymmetrical cortical activation may influence functional asymmetries that can be observed with behavioural tests (Levy, Heller, Banich, & Burton, 1983). Recently, it was shown that individual differences in extent of handedness can partly be attributed to asymmetrical activation of the two cortical hemispheres at rest, measured by EEG (Papousek & Schulter, 1999a).…”
mentioning
confidence: 99%
“…Although accumulating evidence indicates a robust functional link between alpha oscillations and the activity in the visual system, proof of asymmetries in alpha oscillatory patterns is still scarce. Indeed, asymmetries in the alpha range have been mainly investigated in frontoparietal networks and has been linked to psychiatric conditions (Ocklenburg et al 2019 ; Stewart et al 2011 ; Bruder et al 2005 , 2007 ; Metzeger et al 2004 ) or hand preference (Ocklenburg et al 2019 ; Papousek and Shoulter 1999 ). However, recent findings on spatial orienting following directional cues have shown that, while in the left hemisphere alpha power decreases to facilitate visual processing in the contralateral field, alpha activity in the right hemisphere has a dual role in attention shifts.…”
Section: Introductionmentioning
confidence: 99%